Decreasing sperm quality: a global problem? - Blettner Maria; Zeeb Hajo; Merzenich Hiltrud (BMC, 2010)
Abstract Background Carlsen and coworkers (1992) reviewed 61 heterogeneous observational studies on semen quality published between 1938 and 1990. This review indicates that mean sperm density decreased significantly between 1940 and 1990. An extended meta-analysis with 101 studies confirmed a decline in sperm density for the period from 1934 to 1996 (2000). The key message of the meta-analyses is that sperm counts have decreased globally by about 50% over the past decades. This assessment has been questioned. Discussion A major methodological problem of the meta-analysis is the use of data collected in different countries, at different times, on different populations and with different methods of semen analysis. Furthermore, the results of studies concerning semen analysis are frequently biased e.g. by selection criteria of volunteers. In most studies on human semen characteristics the populations under study are insufficiently defined and the study participants are not a representative population sample. The incidence of testicular cancer has increased in Caucasian men worldwide. The investigation of common risk factors for male reproductive disorders requires well designed epidemiological studies and the collection of individual data. Summary Former meta-analyses of sperm count data show a global downward trend. This conclusion should be interpreted with caution. The included studies are of great heterogeneity due to geographical and/or ethnical variation, different study designs and different methodological standards. Population-based prospective studies are needed to investigate secular trends in male reproductive disorders.